2005
DOI: 10.1086/429923
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Community Psychobehavioral Responses During and After the 2003 Outbreak of Severe Acute Respiratory Syndrome in Hong Kong

Abstract: Our findings can assist in modifying public service announcements in the future, which should be tailored to psychobehavioral surveillance intelligence to achieve the desired behavioral outcomes. Future research should explore the use of more-sophisticated techniques, including structural equation modeling and game-theoretical frameworks, to analyze population psychology and behavior, and it should integrate such findings with transmission dynamics modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
339
15
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(423 citation statements)
references
References 18 publications
45
339
15
12
Order By: Relevance
“…One explanation for this discrepancy between our findings concerning the role of receiving information about the outbreak and those of previous studies 9,19,60,67 is that information may have a different effect on vaccine intentions depending on the stage of the outbreak. While the spread of information during the study period had no impact on likely vaccine uptake, stronger associations might have been observed earlier in the swine flu outbreak when members of the public were less certain about the transmission or nature of the illness.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…One explanation for this discrepancy between our findings concerning the role of receiving information about the outbreak and those of previous studies 9,19,60,67 is that information may have a different effect on vaccine intentions depending on the stage of the outbreak. While the spread of information during the study period had no impact on likely vaccine uptake, stronger associations might have been observed earlier in the swine flu outbreak when members of the public were less certain about the transmission or nature of the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…21 Several studies have suggested that media reporting about features of an outbreak, such as the number of cases or deaths, might influence key health behaviours. 9,19,60,67 However, we found no evidence to suggest that how much people had heard about swine flu in the past week affected likely vaccine uptake or that specific aspects of what they had heard had any substantial impact. The only exception was a weak association between having heard that the number of deaths from swine flu had increased recently and greater likelihood of accepting the swine flu vaccine.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Results from a similar study conducted in India showed that about half of 791 respondents in the general community believed that H1N1/09 was caused by pigs [13]. Since it is known that public perception or beliefs about an outbreak is influenced by advice and directives by officials and health-care providers [14], it is most likely that the Tanzanian public had not received correct information and advice during the outbreak of H1N1/09 influenza in the country.…”
Section: Discussionmentioning
confidence: 99%